Dam construction reshapes heavy metal pollution in soil/sediment in the three gorges reservoir, China, from 2008 to 2020 - Xu, Qinqin; Zhou, Kun; Wu, Boran (Frontiers in Environmental Science, 2023)
Dam construction interfered with the original environment of the river system and greatly affected the geochemical behaviors of trace metals. Thus, a set of toxic metals of Cr, Ni, Cu, Zn, As, Cd, Pb and Hg in soil/sediment of the Three Gorges Reservoir (TGR) during the period of 2008 to 2020 were analyzed and summarized. The results showed that levels of trace metals (except Cr) were apparently higher than the soil background in the TGR and China, in which Cu, Zn, As, Cd, Pb and Hg corresponded to the moderately to highly contaminated grade. As expected, most trace metals (except Ni and As) were observed an evident increase after the full impoundment stage of 2008 to 2014, suggesting the dam construction of the TGR that promoting the sediment adsorption effects for trace metals. For spatial patterns, metal levels largely depended on the sampling sites, that intensive anthropogenic activities might well be the primary contributors. Main stream with higher concentrations of trace metals in comparison with tributaries reflected the larger loads of metal pollution. In the water-level-fluctuating zone, hydrological regime induced by damming played a critical role on the redistribution of trace metals through eroding soil/sediment particles or bedrocks and altering the physiochemical characteristics and vegetation coverage of soil/sediment. Finally, submerged sediment seemed as a major sink of trace metals that had greater concentration than that in the water-level-fluctuating zone.